1997
DOI: 10.1136/ard.56.7.421
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced jejunal production of antibodies to Klebsiella and other Enterobacteria in patients with ankylosing spondylitis and rheumatoid arthritis

Abstract: Objective-To measure gut immunity directly in jejunal fluid in patients with ankylosing spondylitis (AS) and rheumatoid arthritis (RA). Methods-Antibodies against three diVerent Enterobacterias were measured in jejunal perfusion fluids (collected by a double balloon perfusion device) of 19 patients with AS, 14 patients with RA, and 22 healthy controls using enzyme linked immunosorbent assay. Results-The AS patients had significantly increased jejunal fluid concentrations of IgM, IgG, and IgA class antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…(11) AS patients were found to have an increased jejunal production of Klebsiella antibodies when compared to rheumatoid arthritis patients or controls [71].…”
Section: Gut As the Main Source Of Klebsiella Infection In "As"mentioning
confidence: 99%
“…(11) AS patients were found to have an increased jejunal production of Klebsiella antibodies when compared to rheumatoid arthritis patients or controls [71].…”
Section: Gut As the Main Source Of Klebsiella Infection In "As"mentioning
confidence: 99%
“…Cellular hyporeactivity of peripheral blood cells to bacterial antigens may reflect defective T-cell responses, allowing bacterial antigens to persist in diseased patients. The predominating IgA antibody responses imply that mucosa, probably the gut mucosa, is important in eliciting these responses [21,22]. Mucosal inflammation has been demonstrated in a large percentage of patients with AS, as in patients with SpA [23••], suggesting that the initial immune responses occur in gut mucosa.…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
“…11 However, we found that intestinal fluid from RA patients contained only low levels of IgA and IgM RF, some 1000 times less than in serum. 15 The IgA, but notably not the IgM, RF activities were generally well correlated with the food antibody levels of all the three Ig classes (r = 0.65 to 0.94; p = 0.01 to 0.0001).…”
Section: Discussionmentioning
confidence: 85%
“…Most of the subjects were included in a previously reported study of microbial antibodies. 15 Jejunal perfusion fluid A segment of the jejunum was perfused, as detailed elsewhere, by a small diameter tube 175 cm long and containing six channels. 16 The original report described the insertion of the tube, gastric drainage, inflation of the balloons, and rinsing of the closed intestinal segment.…”
Section: Study Subjectsmentioning
confidence: 99%